Adaptive re-use of farm structures - Masigan, Orvile V. (Manila : National University, 1998)
The principle of planning small houses and other farm structures require experience and some skills. This study is presented to stimulate designing of good houses and serviceable farm structures at reasonable cost with due emphasis on sound and solid construction.
Chapter I. Introduction -- Chapter II. Terms of references -- Chapter III. Research methodology -- Chapter IV. Design framework -- Chapter V. Analysis -- Chapter VI. Summary and Conclusion -- Bibliography -- Appendices.
Includes bibliographical references.
Keywords: FARM STRUCTURES; HOUSES